SISTEM MONITORING LAPORAN HARIAN AVIATION SECURITY BANDARA SULTAN SYARIF KASIM II BERBASIS ANDROID - Bambang Kurniawan; Muhammad Khaibar Putra Adithia; Septian Simatupang (Nindikayla Institute, 2023)
SSK2 Airport assigns basic duties to AVSEC officers. In performing their duties in accordance with the SOP, officers need to make daily reports that have been done every day. The process of monitoring the daily report of officers is currently still using